Integrando La Música En La Educación Infantil A Través Del Equipo Docente Interdisciplinar - Rosa María Serrano Pastor (European Scientific Journal, ESJ, 2017)
School education is a complex process in which students and teachers interact in a context. In order to obtain an adequate and complete advance in the field of educational research, it is necessary to study in depth the different parts of this process. This article focuses on the study of the interdisciplinary teamwork of teachers in a project on the awareness of the linguistic discourse, verbal and musical, in early childhood education. In this project the generalist teachers carried out the music-verbal activities with their students. The objective of this study was to analyse the influence of the work in teaching team, composed by generalist teachers and music specialist, in this project; examining the parameters that influence its functioning and observing the benefits of its application. The analysis has been carried out from the qualitative methodology, finding that previous knowledge and experience of each teacher, positive interdependence between them, shared responsibility and the role of the music specialist and of the School influence the proper functioning of this group. The teamwork carried out in this project has reported benefits, among which are the production of linguistic knowledge, training and professional development of the teachers involved. It is valued that the project is not only beneficial for students but also for teachers.